The Influence of Pedagogic and Professional Competencies on the Performance of Physical Education Teachers of Elementary Schools in Padang - Masrun Masrun; Damrah Damrah (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2022)
The goals of this research was to analyze the Influence of pedagogic and professional competencies, and its effect on the performance of the Physical Education teacher of the Elementary School level in Padang, West Sumatra. This study applies the causal associative method, and uses  54 samples. The data collection techniques  using tests and questionnaires. The data is processed by using the IBM SPSS software application. The result of this research shows  that from 54 physical education teachers who have competence in the poor category, 63.45%, consisting of pedagogic competence 64.87% is in the less category, and 64.43% professional competence is in the less category. For male teachers, pedagogic and professional competencies are correlated with teacher performance. The data also shows that there are differences in the relationship and influence between the pedagogic and professional teachers of male and female teachers. Based on the analysis, we could make the conclusion that the pedagogical and professional components are the main factors regarding the success of the performance of physical education teachers  at the elementary school level in the city of Padang, West Sumatera.